Targeting Catecholaminergic Systems in Transgenic Rats With a CAV-2 Vector Harboring a Cre-Dependent DREADD Cassette - Cerpa, Juan-Carlos; Marchand, Alain R.; Salafranque, Yoan; Pape, Jean-Rémi; Kremer, Eric J.; Coutureau, Etienne (Frontiers in Molecular Neuroscience, 2020)
Techniques that allow the manipulation of specific neural circuits have greatly increased in the past few years. DREADDs (Designer receptors exclusively activated by designer drugs) provide an elegant way to manipulate individual brain structures and/or neural circuits, including neuromodulatory pathways. Considerable efforts have been made to increase cell-type specificity of DREADD expression while decreasing possible limitations due to multiple viral vectors injections. In line with this, a retrograde canine adenovirus type 2 (CAV-2) vector carrying a Cre-dependent DREADD cassette has been recently developed. In combination with Cre-driver transgenic animals, the vector allows one to target neuromodulatory pathways with cell-type specificity. In the present study, we specifically targeted catecholaminergic pathways by injecting the vector in knock-in rat line containing Cre recombinase cassette under the control of the tyrosine hydroxylase promoter. We assessed the efficacy of infection of the nigrostriatal pathway and the catecholaminergic pathways ascending to the orbitofrontal cortex and found cell-type specific DREADD expression.